Nutrient homeostasis within the plant circadian network - Haydon, Michael J.; Román, Ángela; Arshad, Waheed (Frontiers in Plant Science, 2015)
Circadian clocks have evolved to enhance adaptive physiology in the predictable, fluctuating environment caused by the rotation of the planet. Nutrient acquisition is central to plant growth performance and the nutrient demands of a plant change according to the time of day. Therefore, major aspects of nutrient homeostasis, including carbon assimilation and mineral uptake, are under circadian control. It is also emerging that there is feedback of nutritional status to the circadian clock to integrate these processes. This review will highlight recent insights into the role of the circadian clock in regulating plant nutrition as well as discuss the role for nutrients in affecting circadian function.